Age and composition of crystalline basement rocks on the Norwegian continental margin: offshore extension and continuity of the Caledonian–Appalachian orogenic belt - Trond Slagstad; Børre Davidsen; J.Stephen Daly (2016)
Twenty-two wells on the Norwegian continental margin have penetrated underlying basement. We present U–Pb zircon, whole-rock geochemical, and Sm–Nd and Rb–Sr isotopic data from nine wells in the North Sea and Norwegian Sea with relevance to the offshore continuation of the Norwegian Caledonides, and their correlation throughout the Caledonian–Appalachian orogenic belt. Palaeozoic magmatism in the North Sea can be divided into two groups. The older group consists of 460 Ma calc-alkaline granites with evolved isotopic compositions, correlative with similar rocks in the Uppermost Allochthon. The younger group consists of a 430 Ma dacite and a 421 Ma leucogabbro, with less evolved isotopic compositions. In the Norwegian Sea, isotopically evolved granitic magmatism at 437 Ma and more juvenile dioritic magmatism at 447 Ma are correlative with magmatism in the Bindal and Smøla–Hitra Batholiths in the Uppermost Allochthon. Metasedimentary basement rocks from the North Sea and Norwegian Sea, dominated by Late Palaeoproterozoic and Mesoproterozoic grains, resemble rocks found in the Caledonides of Scotland, Greenland and Svalbard. The new data, along with studies elsewhere along the belt, suggest that similar rocks may exist along much of the orogen.